2022
DOI: 10.3390/foods11213387
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cheese Whey Containing Postbiotics of Lactobacillus acidophilus LA5 and Bifidobacterium animalis BB12 as a Preserving Liquid in High-Moisture Mozzarella

Abstract: High-moisture mozzarella cheese (HMMC) is a highly perishable cheese with a short shelf life. In this study, the effects of UF cheese whey containing postbiotics from Lactobacillus acidophilus LA-5 (P-LA-5), Bifidobacterium animalis BB-12 (P-BB-12), and their combination on the microbial (i.e., psychrophiles, mesophiles, lactic acid bacteria, and mold-yeast population) and sensory properties of HMMC were investigated. Postbiotics were prepared in a cheese whey model medium as a novel growth media and used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The observed effect can also be attributed to the presence of organic acids in the absorbed postbiotics within the yoghurt. These results align with the research conducted by Sharafi et al (2022) , where it was observed that samples containing postbiotics demonstrated a significant reduction in pH values in comparison to the control samples. In another study, treatment with postbiotic decreased the pH values of the breast fillet samples compared to the control samples ( İncili et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The observed effect can also be attributed to the presence of organic acids in the absorbed postbiotics within the yoghurt. These results align with the research conducted by Sharafi et al (2022) , where it was observed that samples containing postbiotics demonstrated a significant reduction in pH values in comparison to the control samples. In another study, treatment with postbiotic decreased the pH values of the breast fillet samples compared to the control samples ( İncili et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Presently, postbiotics derived from Lactobacillus acidophilus LA5 and Bifidobacterium animalis subsp. lactis BB-12 are being utilized in the production of functional foods, especially for cheese products ( Sharafi et al, 2022 ), as well as for modified milk, with their effectiveness assessed in randomized clinical trials. For instance, Bifidobacterium breve and S. thermophilus postbiotics showed a reduction in the incidence of allergy-related symptoms in infants with a positive history of atopy during their early months of life; this effect persisted even after discontinuation of the preparation ( Morisset et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioprotection and biopreservation of dairy products containing microorganisms are novel approaches to food security and conservation (Margalho et al, 2021). Sharafi et al (2022) applied ultrafiltration cheese whey containing postbiotics from Lactobacillus acidophilus LA-5 (P-LA-5), Bifidobacterium animalis BB-12 (P-BB-12) and their combination (P-LA-5 þ BB-12) as a new preserving liquid. A very noticeable reduction (approximately 3 log CFU/g on Day 4) was observed in mold and yeast at samples with postbiotics.…”
Section: Application Of Postbiotics In Foodmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs), the most important postbiotics formed during probiotic fermentation, have biological functions such as reducing the risk of intestinal infections, increasing mineral bioavailability, immunomodulation, hypocholesterolemic, a n t i t u m o r i g e n i c , a n t i i n f l a m m a t o r y , antiproliferative, antiobesogenic, antiallergic, and antioxidant effects (Aguilar-Toalá et al 2021, Salminen et al 2021, Omak & Yilmaz-Ersan 2022, Anvar et al 2023, Asif et al 2023. However, recent studies have focused on the utilization of postbiotics produced by probiotics as a food additive owing to their health and technological effects (Mogahed Fahim et al 2021, Hosseini et al 2022, Darwish et al 2022, Sharafi et al 2022, Anvar et al 2023, Pimentel et al 2023.…”
Section: Introductionmentioning
confidence: 99%